Discrimination of Single Transport Systems : The Na(+)-sensitive transport of neutral amino acids in the Ehrlich cell - Inui, Yukiharu (The Rockefeller University Press, 1966)
Uptake of methionine, α-aminoisobutyric acid, and α-(methyl-amino)-isobutyric acid has been shown to occur by at least two transport systems, one sensitive and the other insensitive to the Na(+) concentration. For α-aminoisobutyric acid and its N-methyl derivative, the Na(+)-insensitive uptake is not concentrative and its rate increases almost linearly with concentration within the range examined. In contrast, the Na(+)-insensitive uptake of methionine is concentrative and subject to inhibition by such amino acids as phenylalanine, leucine, and valine, although not in a manner to indicate that the uptake is mediated by a single agency. This component is not produced by a residual operation of the Na(+)-requiring transport system, handicapped by the absence of Na(+) or by its having combined with α-aminoisobutyric acid. The increase in the rate of methionine uptake is linear with concentration only above about 16 mM methionine. The Na(+)-sensitive uptakes of methionine, α-aminoisobutyric, and α-(methylamino)-isobutyric acid appear to occur by the same population of transport-mediating sites. Both K(m) and V (max) of the Na(+)-sensitive uptake of these three amino acids change with changes in the concentration of Na(+), an effect which is shown to have a theoretical basis. A similarity in the values of Vmax for ten amino acids entering principally by the Na(+)-sensitive agency indicates that differences in their K(m) values probably measure differences in their affinities for that transport-mediating system.